PENEGAKAN HUKUM TERHADAP ANGGOTA POLRI YANG TERLIBAT PENYALAHGUNAAN NARKOTIKA - Ruslan Abdul Gani (Universitas Batanghari Jambi, 2015)
The aim of this study examines the enforcement of the law against members of the police involved in the abuse of narcotics, by stressing first, how the investigation against members of the police who have been involved in the abuse of narcotics in the jurisdiction of Police Jambi, second, penalties / punishment imposed for police officers found guilty misuse of narcotics in the jurisdiction of Police Jambi. The results showed that the investigation into the crime of Narcotics for the individual members of the police involved in drug abuse conducted by investigators Provam Police. Then sanctions / hukumanyang imposed against members of Jambi Police found guilty of abuse of narcotics by petusan court has had permanent legal force, among others: the dismissal with respect (PTDH), the trial of the Code, and the delay of promotion.Keywords: Law Enforcement Against Police Members involved in drug abuse.